Drawing as a Salutogenic Therapy Aid for Grieving Adolescents - Katisi, Masego; Jefferies, Philip; Sebako, Mpho (Arts and Health Promotion: Tools and Bridges for Practice, Research, and Social Transformation, 2021)
The use of drawing in therapeutic contexts creates an empowering platform for young people to express traumatic experiences and serves as a basis for improving their psychosocial health. In the clinician’s repertoire, drawings can be used for the assessment of stressors and risks in order to determine appropriate treatment or to evaluate progress. While important, these clinical approaches may encourage pathologizing clients. A more holistic and positive approach uses drawing to explore young people’s resilience resources, including their Sense of Coherence, despite the experience of stressors. This can contribute to health promotion-focused programming. This chapter explores the health promotion qualities of the use of drawings by describing the case study of Botswana’s Balekane EARTH therapy program, involving 15 adolescents, two young adults, and four of their social workers. The findings resonate with Antonovsky’s theory of salutogenesis, demonstrating movement from disease to positive health. Using a salutogenic lens, we argue that drawing is a critical tool for helping participants express and communicate complex emotional stressors and their impacts, for mapping different potential and existing supporting resources, and for helping themselves to visualize adaptive coping strategies.